Docosahexaenoic acid enrichment in NAFLD is associated with improvements in hepatic metabolism and hepatic insulin sensitivity: a pilot study - Hodson, L; Bhatia, L; Scorletti, E; Smith, D; Jackson, N; Shojaee-Moradie, F; Umpleby, M; Calder, P; Byrne, C (Nature Publishing Group, 2017)
Background/Objectives Treatment of subjects with non-alcoholic fatty liver disease (NAFLD) with omega-3 polyunsaturated fatty acids (PUFA) suggests high levels of docosahexaenoic acid (DHA) tissue enrichment decrease liver fat content. We assessed whether changes in erythrocyte DHA enrichment (as a surrogate marker of changes in tissue enrichment) were associated with alterations in hepatic de novo lipogenesis (DNL), postprandial fatty acid (FA) partitioning, and hepatic and peripheral insulin sensitivity in a sub-study of the WELCOME* trial. Subjects/Methods Sixteen participants were randomized to 4 g/day EPA+DHA (n=8) or placebo (n=8) for 15-18 months and underwent pre- and post-intervention measurements. Fasting and postprandial hepatic FA metabolism was assessed using metabolic substrates labelled with stable-isotope tracers (2H2O and [U13C]palmitate). Insulin sensitivity was measured by a stepped hyperinsulinaemic-euglycaemic clamp using deuterated glucose. Participants were stratified according to change in DHA erythrocyte enrichment (< or ≥2% post-intervention). Results Nine participants were stratified to DHA≥2% (8 randomised to EPA+DHA and 1 to placebo) and seven to the DHA<2% group (all placebo). Compared to individuals with erythrocyte <2% change in DHA abundance, those with ≥2% enrichment had significant improvements in hepatic insulin sensitivity, reduced fasting and postprandial plasma triglyceride concentrations, decreased fasting hepatic DNL, as well as greater appearance of 13C from dietary fat into plasma 3-hydroxybutyrate (all P<0.05). Conclusions The findings from our pilot study indicate that individuals who achieved a change in erythrocyte DHA enrichment ≥2% show favourable changes in hepatic FA metabolism and insulin sensitivity, which may contribute to decreasing hepatic fat content.